Changing the Community Paradigm for Indonesian Immgiration - Budy Mulyawan; Andreas Parulian Pakpahan (Jurnal Abdimas Imigrasi, 2020)
There is a wrong community paradigm about inspiration. The impulse does not merely provide passport making services for the community. But more than that, Immigration has far broader duties and functions than taking care of making passports. There are 4 functions of immigration, including community service, law enforcement, state security and development facilitators. This institution has the duty to guard the country's gates from all threats that can endanger the security and sovereignty of this country. For this reason, community service is carried out in order to change the way people think about immigration in Indonesia. The target is students in one of Bekasi's high schools. It is hoped that they can become actors in disseminating correct information related to immigration tasks and functions and increase the existence of the community. Thus, the entire community can play an active role in helping to realize the security and sovereignty of this country.